Interpretasi Mahasiswa Terhadap Stiker WhatsApp Bernuansa Sarkastik dalam Komunikasi di Grub Kelas STIKOSA-AWS - Firqoh Najiyah; Supriadi (LPPM Stikosa-AWS, 2025)
In the era of digital communication, WhatsApp stickers have evolved into a nonverbal medium that plays a significant role in conveying emotions, humor, and even implicit criticism. This study aims to examine how STIKOSA-AWS students interpret the use of sarcastic WhatsApp stickers in classroom group interactions, particularly within class group chats. The research employs a descriptive qualitative approach with non-participatory observation of chat archives and semi-structured interviews with active group members. The data were analyzed using semiotic analysis and the theory of symbolic interactionism to explore the symbolic meanings and social context behind the use of such stickers. Preliminary findings indicate that the interpretation of sarcastic stickers is strongly influenced by the nature of social relationships among members, prior digital communication experience, and the context in which the stickers are sent. Some students interpret these stickers as a form of humor and familiarity, while others perceive them as offensive or confusing. Sarcastic stickers also function as expressive speech acts and pragmatic strategies to convey criticism or sarcasm in a setting perceived as casual. This study emphasizes the importance of digital communication sensitivity in maintaining harmonious interaction, especially in virtual spaces that are collective and multicultural, such as class WhatsApp groups.